PENYERAPAN HUKUM ISLAM PADA KOMUNITAS ADAT (STUDI ANTROPOLOGI HUKUM DI BADUY, KAMPUNG NAGA DAN MARUNDA PULO) - Abdurrahman Misno (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2017)
The first community to accept Islam was the tenant at the coastal areas of Sumatra,Java, Sulawesi, Kalimantan, Maluku and Nusa Tenggara. After that Islam disseminated to rural  areas  throughout  the country as  the consequence of their reception of Islamic law. However, the fact was not all Islamic law accepted and implemented,  because   they  already   have   customs  practiced   continuously  by hereditary generations long before the arrival  of Islam. Some custom in Indonesia, which still survive was practiced by indigenous community such as Baduy, Kampung Naga and Marunda Pulo. Research shows that the reception of Islamic law by the community of Baduy in the implementation of Islamic law marriage that is reading the creed of the Prophet  Muhammad Pbuh, the presence of dowry and marriage records  by KUA, especially  on  the  community of Outer  Baduy. Meanwhile the community of Inner Baduy has not been  accept the Islamic law a lot in the field of marriage.  Reception  in the field of inheritance was limited to the mention of the terms in Islamic inheritance, while the division still follow their customs that divide the estate  equally both boys and  girls.  While the community of Kampung Naga reception occurs in the majority of law and worship in particular  muamalah espescially in wedding. At issue still retain their inheritance patterns of inheritance according to their customs that divide the inheritance with equal parts between boys and  girls.  Kampung  Marunda  Pulo  reception  of  Islamic  law  in  worship  and muamalah.  Islamic law reception  process  occurs  due to internal  factors  (custom character and creed) and external (social interaction and the power of the state). Keywords:   Reception  of  Law,  Indigenous  Community,  Adat,  Baduy,  KampungNaga, Marunda Pulo and Theory Reception through Selection-modification.